Technostress and emotional exhaustion in higher education: A qualitative-quantitative correlational study among undergraduate and graduate students - Prado-Espinoza, Azucena Natividad; Parillo, Jesus Roger Chavez; Castelo-Collado, Rosario Abigail; Zuñiga-Marino, Miguel Angel; Achata-Gonzales, Gloria Angélica; Ala-Gordillo, Bruceli Benito (Edelweiss Applied Science and Technology, 2025)
This study is situated within the growing dependence on digital technologies in higher education, which has raised concerns about their impact on students’ emotional well-being. The primary objective was to determine the direct relationship between technostress and emotional exhaustion among undergraduate and graduate students, using a qualitative-quantitative correlational design. Two validated instruments were applied: one measuring technostress (assessing skepticism, fatigue, anxiety, and inefficacy) and another evaluating emotional exhaustion (including overload, overexertion, low mood, insomnia, headaches, fatigue, exhaustion, stress, and study overload). The findings revealed that most participants reported low levels of skepticism (51.7%) and fatigue (47.1%), while a significant proportion presented moderate levels of fatigue (46.6%) and anxiety (42%). Emotional exhaustion emerged intermittently in dimensions such as tension, insomnia, and fatigue. In addition, a noticeable decline in interest in ICT and feelings of frustration associated with their use were identified. Overall, the results confirm a direct relationship between technostress and emotional exhaustion, highlighting the urgency of developing targeted interventions to improve academic well-being.